2013
DOI: 10.1139/cgj-2012-0428
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of reverse end bearing of offshore shallow foundations

Abstract: An experimental investigation of Mana/Gourvenec/Randolph reverse end bearing of offshore shallow foundations 2 ABSTRACT Shallow skirted foundations can mobilise uplift resistance from end bearing in the short to medium term. However, uncertainty exists over the magnitude of reverse end bearing resistance compared with resistance in compression, and how this might be affected by a gap between the external face of the foundation skirt and the adjacent soil. The study presented in this paper explored the problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 27 publications
(24 reference statements)
2
16
0
Order By: Relevance
“…The reduced peak uplift resistance observed may result partly from overloading during the jacked installation, leading to some remoulding of the soil -a characteristic that has been observed in previous tests (Mana et al, 2012c). The reduced peak uplift resistance may also be partly due to vibration of the tool table leading to minor cyclic loading of the foundation and a weaker reverse end bearing failure mechanism.…”
Section: Undrained Capacity In Compression and Uplift With Intact Skisupporting
confidence: 52%
See 1 more Smart Citation
“…The reduced peak uplift resistance observed may result partly from overloading during the jacked installation, leading to some remoulding of the soil -a characteristic that has been observed in previous tests (Mana et al, 2012c). The reduced peak uplift resistance may also be partly due to vibration of the tool table leading to minor cyclic loading of the foundation and a weaker reverse end bearing failure mechanism.…”
Section: Undrained Capacity In Compression and Uplift With Intact Skisupporting
confidence: 52%
“…Each of these issues have been addressed by previous research projects, results of which have provided increased confidence in relying on reverse end bearing for transient and limited sustained uplift (e.g. Gourvenec et al, 2009;Mana et al, 2012a) but caution over the effect of gapping -which can jeopardise the sustainability of reverse end bearing (Acosta-Martinez et al, 2010;Mana et al, 2012c). Experimental studies comparing the uplift response of skirted foundations with an intact and gapped skirtsoil interface have shown that, while full reverse end bearing can be mobilised with a sealed foundation with an intact skirt-soil interface, undrained uplift capacity is severely affected by loss of suction at small foundation displacements in the case of a gapped interface (Acosta-Martinez et al, 2010;Mana et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…However, the reliability of under-base suction is conditional. Perforations of foundation base plates [10,11], loss of sealing through a drainage or vent valve, or a vertical gap along a skirt-soil interface for skirted shallow foundations [12] can provide access to free water and lead to dissipation of suction at the underside of the foundation. Sparse literature is available for shallow foundations under general loading with an interface unable to sustain tension, often referred to as a 'zero-tension' interface.…”
mentioning
confidence: 99%
“…The undrained response in the HV plane and MV plane is symmetric around all axes, assuming full reversed end bearing for tension loads (Mana et al, 2013). Hence, one quadrant gives a full description of the full 360°failure envelope.…”
Section: Load Axis Symmetry Of the Failure Envelopesmentioning
confidence: 99%